Use of immune activated cellular therapy and risks with antibiotic administration in treatment of septic arthritis - Pezzanite, Lynn M., author; Dow, Steven, advisor; Goodrich, Laurie, advisor; Hendrickson, Dean, committee member; Santangelo, Kelly, committee member; Stoneback, Jason, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.